Nuclear disarmament through a realist-liberal-constructivist Mosaic - Nah, Liang Tuang (2015)
Nuclear weapons are unrivalled as tools of destruction, are extremely difficult to defend against, and are proverbial double edged swords, being capable of both enforcing stability in international relations through deterrence and inflicting unfathomable casualties. Bearing this in mind, the current non-proliferation regime depends on consensual compliance with nuclear weapons free norms. Consequently, this dissertation seeks to analyse the cases of South Africa, Ukraine and North Korea using a tripartite framework drawn from national security based realist, economic interdependence based liberalist and moral norms based constructivist factors so as to understand the motivations for nuclear arms development in South Africa and North Korea, and the arguments for nuclear arms retention after Ukrainian independence. Thereafter, this tripartite theory approach will be used to examine subsequent motivations for nuclear disarmament and relinquishment in South Africa and Ukraine while attempting to account for unprecedented nuclear weapons policy transparency and tentative disarmament seen in North Korea from 2007 – 2008. Additionally, the nuclear weapons relinquishment of Belarus and Kazakhstan will be examined and dismissed as subsidiary cases. By analysing these five case studies using this eclectic theoretical framework, common security, economic and norms based motivational drivers can be detected across nuclear proliferants and former proliferants who choose to practice nuclear arms abstinence. By identifying similar decisional drivers for nuclear weapons aspirants/retainers and states completely or partially relinquishing nuclear arms, the determination of potential nuclear armaments proliferators can be evaluated, while nuclear arms possessors like North Korea or suspected nuclear aspirants like Iran could be encouraged to disarm or limit their nuclear activities, thereby strengthening nuclear disarmament policies.